Teknologi Desain Kemasan Dalam Upaya Peningkatan Value Added Produk Usaha Kecil dan Menengah - Putri , Gustiarini Rika; Lubis, Rizki Fadhillah; Arsil, Fikri; Sitorus, Tosty Maylangi; Zulhamidi, Zulhamidi; Siregar, Rahmad Syukur (Politeknik ATI Padang, 2023)
This community service activity aims to provide understanding and skills to MSME actors about the importance of packaging and packaging design. This activity is carried out by providing counseling, training, and assistance to business partners regarding product packaging. The result of this activity is that all partners understand the importance of packaging as added value and branding for their products, and as many as 50% have succeeded in designing packaging independently. In the future, it will be better to have knowledge and skills related to digital marketing to reach consumers even further.